Seroprevalence of Hepatitis B Virus in HIV Tested Positive Patients Accessing Treatment in Specialist Hospital Jimeta - Mohammed Bashir; Halima Ibrahim; Halima Isa (Dr. Sulaiman Al Habib Medical Journal)
Background: Human Immunodeficiency Virus (HIV) positive patients are likely to be at risk of other infectious pathogens such as Hepatitis B Virus (HBV). HIV and HBV are blood-borne pathogens and are transmitted via intravenous drug use, sexual contact, or mother to child during pregnancy or birth. Objective: The present study aimed at determining the seroprevalence of HBV infection among HIV infected patients who are on antiretroviral treatments in Specialist Hospital Jimeta. Methodology: A hospital-based cross-sectional study was conducted among 246 patients from August 2019 to January 2020 at Jimeta Specialist Hospital, Adamawa state, Nigeria. The presence of HBV was detected using DiaSpot Hepatitis B Surface Antigen (HBsAg) kit, whereas demographic data were obtained using a prestructured questionnaire. In the HBsAg detection test, a small quantity of blood was collected using pasture pipette and centrifuge, and then three drops of the plasma were dropped on the test portion of the strip and left for 15 min; the results were then recorded. Data were analyzed using SPSS for Windows version 25.0 and presented in the form of texts, frequency tables, percentage, and graphs; association was assessed using chi-square test, in which p < 0.05 is considered statistically significant. Results: Out of 246 HIV positive individuals screened for the presence of HBsAg, 27 (11.0%) were positive; 21 (8.6%) were female and six (2.40%) were male. Overall, 14 (51.9%) of the participants are non-educated. The highest prevalence was obtained in the age group of 31-45 years with 16 (59.3%). Moreover, most HIV patients who were HBV positive were single with a prevalence of 15 (55.6%), and 210 (38.7%) have knowledge and understanding of vaccination. Conclusion and Recommendation: Higher proportions of HIV positive patients are non-educated. Similarly, HIV positive patients who are 30 years or older should always be checked for HBV infection. In particular, HIV positive patients should be screened frequently for the presence of HBsAg during their hospital visit.